Pierre Clément – prekursor tematyki wolnomularskiej w dramacie - Śrama, Marcin (Studia Europaea Gnesnensia, 2020)
The paper is concerned with the life and work of Pierre Clément, a Geneva-born journalist, dramatist and poet, who was one of the first to make a freemason a protagonist in a play. Issues re- lating to that author have not been discussed in Polish so far, even though Clément was a significant figure in French playwriting as the precursor of Masonic themes